Anticandidal in vitro test of crude ethanol extract of pliek u on the growth of Candida albicans - . Nurliana; . Rinidar; Dian Masyitha (Syiah Kuala University, 2011)
This research was conducted to know the activity of crude ethanol extract of pliek u (E) through in vitro assays. Pliek u obtained from households industry in the Reudep village Aceh Besar, Aceh province. Yeasts used in clinical trials is Candida albicans isolates obtained from the Mycology Laboratory of the Faculty of Veterinary Medicine, Bogor Agricultural University. Anticandidal activity was determined on a paper disc, whereas in the broth dilution method is used to set a killing time activity of the E. The concentration of E that is used to determine the killing time activity is the value of LC50. Crude ethanol extract of pliek u (E) showed anticandidal activity with inhibitory zone diameters of 10.67 ± 0.47 mm. Ethanol extract of pliek u at a concentration of 3.36 mg / ml can reduce the number of C. albicans within two hours at 2.57 log CFU / ml compared to controls at 7.42 log CFU / ml. Based on this study can be concluded that ethanol extract of pliek u (E) can be considered an alternative drug for treating candidiasis, so it needs further research to veterinary clinics in vivo applications